A review on the integration of cloud computing and internet of things - Angelin Jebamalar, J; A. Sasi Kumar, Dr (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) is a technology of interest, becoming so invasive which generate huge amount of data and hence it is significant to integrate with Cloud computing, a delivery model provisioned with virtual resources and storage capacity. This IoT and Cloud computing integration referred as 'Cloud of Things' bears key issues and the one is Security which hampers growth of it. This paper highlights those key issues and smart applications of Cloud of Things.Â Â